PERBEDAAN HASIL BELAJAR PADA MATA KULIAH GAMBAR TEKNIK BERDASARKAN SEKOLAH ASAL MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN S1 JURUSAN TEKNIK SIPIL UNIVERSITAS NEGERI PADANG - 405-413 , Rovi Febrianta (CIVED, 2014)
ABSTRACT   In general , upper secondary education ( high school ) in Indonesia consists of three institutions namely High School ( SMA ) , Aliah Madrasah ( MA ) and Vocational School ( SMK ) . SMA and MA aims to educate students / i continue kejenjang higher studies like college or university , while vocational aims to educate students / i be a middle-level manpower , even though they are also able to continue the high keperguruan . The success of education at high school level , both SMA / MA or SMK will affect learning outcomes in higher education at the college .This research is a comparative study that aims to investigate differences in learning outcomes at the course Engineering Drawing by the student's home school Education Program S1 Building Engineering Department of Civil Engineering , State University of Padang . The research hypothesis that there are differences in learning outcomes at the course Engineering Drawing by the student's home school Education Program S1 Building Engineering Department of Civil Engineering , State University of Padang . The population in this study were all students of UNP PTB FT class of 2009 , 2010, 2011 and 2012 were studied Engineering Drawing courses totaling 211 students . Stratified sampling technique that is proportional random sampling with a sample of 165 students .Based on the results of independent test samples t tests showed results of Self Development significance value 0.000 < 0.05 Ho rejected , Projection 0.284 > 0.05 Ho accepted and for Value Figure 0.043 < 0.05 Ho rejected 0,803 > 0.05 , then Ho is rejected , there is a difference in learning outcomes eye college engineering drawings between students from high school and college students from SMK . Proven hypothesis described . based on the results of research using SPSS to test independent samples t tests showed results of significant value for the principal sub Basic Drawing Skills and 0.000 > 0.05 means that Ho is rejected , subject to sub Projection significance value 0.284 > 0.05 means that Ho is accepted and for Learning Outcomes Picture technique with 0.043 significance value of <0.05 means that Ho is rejected , there is a difference of learning outcomes between technical drawing courses from high school students and students from SMK . Proven hypothesis described . Based on the research results can be seen in the average value ( mean ) dati students from high schools and students from SMK , the principal sub Basic Drawing Skills and 73.1323 and 81.7608 , the principal sub 74.7860 and 73.6199 and Projections Average Picture Learning Outcomes 73.9591 Engineering and 77.6904Berdasarkan research conducted it can be concluded that this could happen because when viewed from the side of the stimulus received tiori learning different vocational students with students of SMA / MA , so they give a different response . Students are more focused on the practice of vocational / pisikomotor , while high school students are more focused to koknitif / thinking .   Keywords : learning outcomes , engineering drawings , and the school of origin